Social Information Retrieval for Online Community Question Answering Services - Lee, Jun Choi; Cheah, Yu-N; Cheah, Wai Shiang (2016)
Online Community Question Answering Services is a platform that allows users to seek for answers anytime and anywhere. The services cover a large collection of unstructured knowledge and become a knowledge repository for problem solving. The answers in the services are generated by other public user. This environment creates a large collection of unstructured knowledge, which can be use as knowledge source for other intelligent processes. From the review, it is a challenge to access accurate information from the Online Community Question Answering services. This study propose a social information retrieval method to access the knowledge from the services. The proposed method query and retrieve information the online services through query expansion. Then, the retrieved information is filtered through a similarity analysis between a question with a query statement and semantic relatedness between answers and the query statement. The accuracy of the proposed approach is evaluated through human evaluation.